2000
DOI: 10.22201/igeof.00167169p.2000.39.3.327
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of radon anomalies with microseismic events in Kangra and Chamba valleys of N-W Himalaya

Abstract: El monitoreo de radón en Palampur y Dalhousie, en los valles de Kangra y Chamba, utiliza la emanometría por medicióndiscreta de radón desde 1992, dentro del programa de Sismicidad del Himalaya del gobierno de la India. Se observa una correlaciónen ambas regiones investigadas con el número de microtemblores registrados por el Departamento de Meteorología de la India enel período 1992-1997. Se estudió el efecto de parámetros meteorológicos (temperatura, precipitación, humedad y velocidad delviento) sobre el nive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The radon and thoron increases which lasted for about 8 h (Figure 8) agree well with the results of the work [26], where increases of these emanations in soil gas were simultaneously observed in an active fault region before earthquakes with the magnitude M L ≥ 4.5, R < 150 km. They usually appeared 1-20 days before an event and had the least duration of 5-7 h. Impulsive radon spikes in soil-gas before weaker earthquakes (1.7 ≥ M ≥ 4.5) were described in the work [30].…”
Section: Observations At "Karymshina" Sitementioning
confidence: 95%
“…The radon and thoron increases which lasted for about 8 h (Figure 8) agree well with the results of the work [26], where increases of these emanations in soil gas were simultaneously observed in an active fault region before earthquakes with the magnitude M L ≥ 4.5, R < 150 km. They usually appeared 1-20 days before an event and had the least duration of 5-7 h. Impulsive radon spikes in soil-gas before weaker earthquakes (1.7 ≥ M ≥ 4.5) were described in the work [30].…”
Section: Observations At "Karymshina" Sitementioning
confidence: 95%
“…Long term dynamical pattern of Radon and Thoron Time Series can be explored for many useful purposes. Various studies found in literature has established the important role of radon for forecasting earthquake [2][3][4][5][6][7][8][9][10][11][12]. Some studies, found in literature, indicates that the behavior of soil radon gas is not linear rather nonlinear dynamics associated with the transport of soil radon gas can give better understanding of time series [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Anomalous radon concentrations, once determined in an active fault zone, could provide information on gas conduits since enrichment processes and upward migration occur [8][9][10]. The so-called Radon Method (RM), as often referred to in radon survey technique, has been applied successfully to detect hidden faults [8] including earthquake and magmatic activity [11][12][13][14][15][16], and volcanic activity [17]. Munadi et al [18] studied the soil gas radon in Indonesia for hydrocarbon exploration localizing hydrocarbon-rich regions that either have or have not been so far exploited.…”
Section: Introductionmentioning
confidence: 99%